Large Scale Land Acquisition and the Violation of Local Communities’ Substantive Rights in Cameroon: The Need for a Rights-Based Approach to Land Governance - Njeng Chuyeh Desmond (Zien Journals, 2021)
The Violation of human Rights as a result of Large-scale land Acquisition practice in Africa and Cameroon in particularly is a perennial concern for local communities. This article explores the human rights impacts of large-scale land acquisition on Local Communities’ Substantive Rights in Cameroon and discusses ways of ameliorating its effects. The article begins by examining substantive rights relevant to the practice of large-scale land acquisition at stake and demonstrates how large scale land acquisition practice in the country undermines substantive rights of rural communities, including land right, right to food and environmental rights in Cameroon based on published materials such as reports, textbooks thesis and journal articles. Next, the article stresses the need for the proper implementation of the procedural rights aspect of a rights-based approach to large-scale land investment governance in the country to achieve a win-win outcome. The last section dwells on conclusion and recommendation
Keywords: Large Scale Land Acquisition; Rights- Based Approach; Governance; Cameroon